Barium titanate based paraelectric material incorporated Poly(vinylidene fluoride) for biomechanical energy harvesting and self-powered mechanosensing. (January 2023) - Maity, Sourav; Sasmal, Abhishek; Sen, Shrabanee
Abstract: Being a superior dielectric material exhibiting low loss, x = 0.4 composition of Ba1-x Srx TiO3 nanoparticles have been widely used as fillers in poly(vinylidene fluoride) (PVDF) for efficient flexible dielectric and electrical energy storage application. The mentioned composition of the material is also very attractive choice of interest to the researchers due to its ability of ferroelectric to paraelectric phase transition. Due to its paraelectric nature, Ba0.6 Sr0.4 TiO3 has not been used for mechanical energy harvesting application till date. Here we have used Ba0.6 Sr0.4 TiO3 particles as fillers in PVDF matrix for efficient mechanical energy harvesting purpose. In the present work, along with the flexible dielectric, ferroelectric and energy storage applications, the developed composite films have been explicitly used for efficient biomechanical energy harvesting, powering small electronic devices and pressure sensing. The fabricated nanogenerator successfully generated a maximum output voltage and output power density of 15 V and 6.75 μW/cm 2 respectively on repeated human finger tapping. The obtained output power has been clearly explained on the basis of polar phase formation and consideration of stress concentration effect. Graphical abstract: Ba0.6 Sr0.4 TiO3 /PVDF composite shows good piezoelectric, energy harvesting and mechanosensing performance along with excellent dielectric and energy storage properties. Image 1